Weyl geometry, topology of space-time and reality of electromagnetic potentials, and new perspective on particle physics. (23rd November 2020) - Tiwari, S C
Abstract: Consistency of Weyl natural gauge, Lorentz gauge and nonlinear gauge is studied in Weyl geometry. Field equations in generalized Weyl-Dirac theory show that spinless electron and photon are topological defects. Statistical metric and fluctuating metric in 3D space with time as a measure of spatial relations are discussed to propose a statistical interpretation of Maxwell field equations. It is argued that physical geometry is an approximation to mathematical geometry, and 4D relativistic spacetime is essentially 3D space with changing spatial relations. The present work is suggested to have radical new outlook on elementary particle physics.